PERAN DAN STRATEGI MANAJEMEN PENDIDIKAN DALAM MEWUJUDKAN SEKOLAH BERKUALITAS - Tiara Puspa Tsurayya; Bahrani; Sudadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education is an important part of life because through education, individuals can develop the knowledge, skills, and attitudes needed in everyday life. However, the quality of education is not only determined by the learning process in the classroom but is also influenced by how educational management is implemented in schools. This study aims to examine the role of educational management in achieving quality schools and to identify strategies that can be used to improve the quality of education. The method used in this study is a literature review, which involves collecting and analyzing various sources such as books, journals, and previous research relevant to the topic. The collected data are then analyzed by understanding, comparing, and organizing information from different sources into a coherent whole. The results show that educational management plays an important role in managing teachers, students, and the curriculum so that the learning process can run effectively. In addition, strategies such as supervision, training, evaluation, and communication also have a significant influence on improving the quality of education. If these management practices and strategies are implemented properly, school activities can run in a more organized way, the learning environment becomes more conducive, and the quality of education can gradually improve.